Europe and the Habsburg Question, 1916-1955 - Buckley, Niall Michael (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2026)
Challenging an established consensus in academic historiography which pronounces the fall of the Austro-Hungarian Monarchy as the definitive conclusion of the Habsburg saga, and with it the Reichsidee dream of a supernatural and supranational political order this doctoral thesis investigates the under appreciated continued role played by the Habsburg dynasty within European modernity between 1916 and 1955. By careful examination of Emperor-King Karl, his wife Zita and son Archduke Otto, it will be argued that throughout their short reign and lengthy exile, these advocates for a Catholic traditional political order in Central Europe became a persistent rallying-point for Interwar, Second World War and early Cold War reactionaries of various political persuasions. Presenting an in-dept transnational study of the Habsburg Question as a matter which intersects with meaningful concepts such as political legitimacy, Central European identity, and Catholic political theory; this study explores counter-narratives to the advance of a 20th-Century European modernity shaped by opposing ascendent Wilsonian principles of enlightenment naturalism, Liberal Democracy, Nationalism and Republicanism. Making use of a wide variety of archival sources including recently made available Vatican documents the efforts of Habsburg exiles and domestic advocates to re-insert themselves into European public life are assessed within the context of polemics concerning Third-Way Political Catholicism and its associated allegations of coinciding Clerical-Fascism and anti-Semitism. Making the argument for the importance of mutually unshakable perceptions of nebulous conspiracies of freemasonic intrigue, Judo-Bolshevik subversion, and opposing monarchist machinations which permeated 20th-Century Central Europe; this thesis concludes that the power vacuums and general crises of legitimacy faced by the new so-called "mushroom republics" of Central Europe necessitate a re-evaluation of the Habsburg legacy in favour of the dynasty's indefatigability in the face of calumny, ridicule, and persecution. Adamant to not fade away into obscurity as had so many other comparable dynasties in an unceasing balance of tradition and reform, Karl, Zita, and Otto remained ever vigilant as to favourable circumstances to forward the Habsburg Reichsidee. They were prepared to re-brand the dynasty in accidental qualities to align with geopolitical realities of their time, but, nevertheless, remained intransigent in their refusal to compromise fundamental claims to hereditary right, Catholic social teaching and supranational outlook.
APPROVED
Keywords: Legitimism; Reichsidee; Austria; Hungary; Habsburg; Monarchism; Political Catholicism; Catholic Social Teaching; Church-State Relations; Political Violence; Vatican; Integralism; Antisemitism; migr